(untitled) (Eurasian Journal of Ecology, 2022)
The article deals with the analysis of the impact of vehicles on the pollution of the air basin of the city of Almaty with emissions of toxic substances. By analyzing and processing information from vari- ous sources, the causes and serious consequences of air pollution by vehicles were shown. Recently, as is known, more than 90% of all carcinogenic substances polluting the air environment of the city of Almaty account for the annual increase in road transport. The results of our study on the degree of intensity of traffic of cars and trucks showed that the largest number of motor vehicles in Almaty falls on Raiymbek (30.4%), Ryskulov (28.1%), Sain (24.3%) and Al- Farabi (12.8%), the smallest number of cars is observed on Seifullin (5.7%) and Nazarbayev (5.5%) avenues. The largest number of trucks falls on Ryskulov (28.1%), Raiymbek (24.1%), Sain (22.4%) and Al-Farabi (12.7%) avenues, and the smallest number of them is the same as cars, i.e. Seifullin Avenue (7.2%) and Nazarbayev Avenue (5.2%). In order to improve the air environment of the city of Almaty, it is necessary to take measures that will contribute to the greening of vehicles, reduce negative trends in air pollution from stationary sources in the city, increase the connection of private houses to gas and expand the areas of green spaces in the metropolis. Key words: Almaty, metropolis, vehicles, air basin, toxic substances.